الامتيازات الجبائية ودورها في دعم الاستثمار السياحي - الهادي, قطرون; عبد الباري, كرمادي; ياسين, كركه (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة الى دراسة دور الامتيازات الجبائية في تدعيم الاستثمارات السياحية، لمعالجة هذا البحث اعتمدنا على المنهج الوصفي لتوضيح الإطار النظري لكل النظام الجبائي الجزائري والامتيازات السياحية، أما الجانب التطبيقي فقد اعتمدنا على منهج دراسة حالة من خلال تصميم استبيان تضمنت الجوانب الرئيسية لمحاور البحث، وقد تم توزيع 90 استمارة على مجموعة من موظفي القطاع السياحي، والفنادق والوكالات السياحية وخبراء سياحيين، وتوصلنا الى مجموعة من النتائج أهمها: -هناك دور للامتيازات الجبائية في دعم الاستثمارات السياحية. -توجد علاقة بين النظام الجبائي والاستثمار السياحي. -توجد امتيازات جبائية في مرحلة انجاز المشروع السياحي. -تتحصل الشركات السياحية على امتيازات جبائية في مرحلة الاستغلال " "This study aims to study the role of tax concessions in supporting tourism investments. To address this research, we relied on the descriptive approach to clarify the theoretical framework for all the Algerian tax system and tourism concessions. As for the practical side, we relied on a case study approach by designing a questionnaire that included the main aspects of the research axes. 90 questionnaires were distributed to a group of tourism sector employees, hotels, tourism agencies and tourism experts, and we reached a set of results, the most important of which are: -There is a role for tax concessions in supporting tourism investments. -There is a relationship between the tax system and tourism investment. - There are tax concessions at the stage of realizing the tourism project. -Tourist companies obtain tax concessions during the exploitation phase "
Keywords: النظام الجبائي، الامتيازات الجبائية، الاستثمارات السياحية; tax system, tax concessions, tourism investments